Integrating Islamic Values into Discipline Management: A Conceptual Study of the POAC Framework in Pesantren - Wafda, Mahfud; Sukarman, Sukarman; Khoiruddin, Muhammad; Kindi, Farhan Afif Al (HEUTAGOGIA: Journal of Islamic Education, 2025)
This study aimed to formulate a conceptual model of disciplinary management in pesantren by integrating core Islamic ethical values into the POAC (Planning, Organizing, Actuating, Controlling) managerial framework. Using a Systematic Literature Review (SLR) with the PRISMA protocol on 12 studies (2020-2025), the research identified six foundational values—ṭāʿah, amānah, shūrā, uswah ḥasanah, iḥsān, and murāqabah—systematically embedded across all four managerial functions. The findings show pesantren discipline is rooted in internalization and spiritual consciousness, contrasting with coercive approaches. Mapping these values onto POAC provides a structured synthesis bridging classical Islamic ethics with modern management. Theoretically, this model advances the field of Islamic Education Management by offering a rigorous value-based managerial framework. Practically, it serves as an operational reference for leaders to design spiritually grounded and administratively coherent discipline systems relevant to contemporary challenges. The study is limited by its conceptual, SLR-based nature, restricting conclusions to theoretical interpretations. Future research must empirically validate this model through field studies, case studies, or comparative analyses across diverse pesantren contexts.